Peningkatan Hasil Belajar PAI Kelas IV dengan Metode Card Sort di UPTD SDN 02 Gunuang Malintang - Sasri Wahyuni; Leni Marsanti; Sri Dewi Mulyani; Roza Elfira; Fadhila Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The card sort method can be used as an alternative method which is felt to better understand the characteristics of students. This research aims to improve student learning outcomes on Asmaul Husna's Example material by applying the Card sort method in class IV UPTD SDN 02 Gunuang Malintang with the variable that is the target of change in this research is learning outcomes, while the action variable used in this research is the method Card sort. This research is classroom action research carried out in 2 cycles, each cycle consisting of 4 stages, namely planning, implementation/action, observation/observation, and reflection. The data collection techniques used are observation and tests. Based on the research results, it can be concluded that student learning outcomes continue to increase until they reach a significant increase. The data description shows that there has been an increase in the value of student learning outcomes. This can be seen from the class average score in the initial observation (pre-cycle) from 66 to 72 in cycle I and 82 in cycle II. Classical completeness was 39% in the initial observation, rising to 62% in cycle I and 90% in cycle II. Thus, a recommendation can be put forward that the application of the Card sort method can improve student learning outcomes in the Noble Asmaul Husna Example material for the 2024/2025 academic year.